Pengaruh Minat Terhadap Hasil Belajar Geografi Dengan Model Inkuiri Terbimbing Di SMAN 3 Samarinda - Yeftha, Yeftha; Haryanto, Zeni; Saputra, Yulian Widya (geoedusains: Jurnal Pendidikan Geografi, 2020)
Learning by mentoring the teacher is able to attract interest and straighten the concept when students conclude the results of their investigation. This study aims to determine the effect of interest in the learning outcomes of students of class X MIPA 5 in SMA Negeri 3 Samarinda. This type of research is quantitative that is cause and effect where the independent variables student interest and dependent learning is student learning outcomes. This research is assisted with intermediate variables namely guided inquiry models. Sampling by purposive sampling from the whole population of class X obtained a sample of 31 students. Data collection in this study was conducted using two ways, namely, a questionnaire to determine student interests and post test questions to determine student learning outcomes. The results of this study indicate the average value of student learning outcomes with a value of 76.00. While the average acquisition value of student interest is 75.54. The correlation coefficient obtained by 0.048 which means that shows the close relationship between X (interest) and Y (learning outcomes) and the magnitude of the determinant coefficient given by X to Y is 12.8%. Then it can be seen that the tcount = 2.066 with a sig value of 0.048 <0.05 then Ha is accepted and H₀ is rejected, which means there is an influence between the variable of interest (X) on the variable of student learning outcomes (Y).